Application of KANO’s Model for Measuring Market Orientation of Higher Education in Indonesia Based on Student’s Perspective - Moh Farid Najib (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Abstract— This paper aims to understand what are the requirement of market orientation attributes as well as categorize the necessary requirements of higher education in Indonesia. Kano’s model used to identify the attributes that better service can improve customer satisfaction levels. Kano’s model is widely used in the area of quality management and product or service innovation. The research was using a Kano’s model with 200 respondents from students of higher education. The results of this study found that the market orientation attributes identified into three categories. They are one-dimensional attribute requirements and indifferent attribute requirements. This model illustrated through a case study of Indonesian higher education.